The Indonesia Spice Up The World (ISUTW) Campaign As An Indonesian Nation Branding Effort: Kampanye Indonesia Spice Up The World (ISUTW) Sebagai Upaya Nation Branding Indonesia - Parmato, Diaz; Darman Moenir, Haiyyu; Elian Nasir, Putiviola (Hubungan Internasional Universitas Andalas, 2023)
The development of globalization throughout the world also affects the interaction between state actors in the international system, especially in the practice of diplomacy carried out by states. One form of diplomacy that has developed is the gastrodiplomacy campaign carried out by Indonesia. At the end of 2020, an Indonesia Spice Up the World (ISUTW) gastrodiplomacy campaign was initiated which was initiated by the government and across ministries in Indonesia with the aim of increasing exports of Indonesian spices and local culinary seasonings and expanding the network of Indonesian restaurants abroad as one of the efforts in Indonesia's national economic recovery after the Covid-19 pandemic. The purpose jncarried out by Indonesia through the Indonesia Spice Up the World (ISUTW) campaign. Gastrodiplomacy campaigns carried out by a country can be analyzed through nation branding strategies in seeing how the strategy can achieve a country's national interests. The research was conducted using the conceptual framework of